2008
DOI: 10.1111/j.1574-6968.2008.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

From yeast killer toxins to antibiobodies and beyond

Abstract: Antibiobodies are paradigmatic of yeast killer toxin (KT)-like antibodies (KAbs) mimicking the antimicrobial activity of KTs in the frame of the yeast killer phenomenon. Polyclonal, monoclonal and recombinant anti-idiotypic antibiobodies (anti-idiotypic KAbs), internal images of a wide-spectrum KT produced by the yeast Pichia anomala (PaKT), have been produced by immunization with the idiotype of a PaKT-neutralizing monoclonal antibody. Anti-idiotypic KAbs showed microbicidal activity against eukaryotic and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 59 publications
4
27
0
3
Order By: Relevance
“…A subset of killer toxin-like Abs (KT-Abs), produced by idiotypic vaccination with mAb KT4 that was raised to neutralize a KT produced by Pichia anomala, showed broad antimicrobial activities in vitro against pathogenic bacteria, protozoa, and fungi (3,35) and provided protection in experimental models of local and systemic fungal infections (36,37). These Abs functionally mimic the cytotoxic action of the P. anomala KT, which has wide-spectrum antimicrobial activity against prokaryotic and eukaryotic microorganisms presenting receptors for KT (38). Similar activities were observed with KT-mAb and its recombinant KT-scFv (3,(35)(36)(37)39).…”
supporting
confidence: 55%
“…A subset of killer toxin-like Abs (KT-Abs), produced by idiotypic vaccination with mAb KT4 that was raised to neutralize a KT produced by Pichia anomala, showed broad antimicrobial activities in vitro against pathogenic bacteria, protozoa, and fungi (3,35) and provided protection in experimental models of local and systemic fungal infections (36,37). These Abs functionally mimic the cytotoxic action of the P. anomala KT, which has wide-spectrum antimicrobial activity against prokaryotic and eukaryotic microorganisms presenting receptors for KT (38). Similar activities were observed with KT-mAb and its recombinant KT-scFv (3,(35)(36)(37)39).…”
supporting
confidence: 55%
“…It has been shown that the killer toxin produced by W. saturnus has many applications (Magliani et al 2008). In order to increase the activity of the killer toxin, it is necessary to disrupt the WsEXG1 gene in W. saturnus WC91-2.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the toxin-producing killer yeasts have been identified in the genera Candida, Cryptococcus, Debaryomyces, Hanseniaspora, Hansenula, Kluyveromyces, Metschnikowia, Pichia, Saccharomyces, Ustilago, Torulopsis, Williopsis, Mrakia, and Zygosaccharomyces, indicating that the killer phenomenon is indeed widespread among yeasts (Magliani et al 1997;Hua et al 2010). Among them, the killer toxins produced by different species of Williopsis and Pichia have received increasing attention because they can kill a wide range of sensitive microorganisms including the pathogenic Candida albicans and some filamentous fungi and bacteria (Magliani et al 2008). Much research has shown that killer yeasts can be applied to control the growth of pathogenic yeasts in humans, animals, and plants .…”
Section: Introductionmentioning
confidence: 98%
“…However, although some researchers have shown that topical applications in the treatment of superficial lesions might well be possible, one drawback of most yeast killer proteins is that they exhibit their cytotoxic activity only at temperatures between 20°C and 30°C within a narrow pH range [53,54]. Therefore, yeast toxins are unsuitable as direct applications for oral and/or intravenous administration [55]. Killer toxins, however, fuelled the development of new antifungal agents that mimick the antimicrobial activity of killer toxins, so-called killer antibodies and killer antibodyderived peptides.…”
Section: Mycoviruses and Toxinsmentioning
confidence: 99%
“…These derivatives have shown activity against various human fungal pathogenic fungi including C. albicans and may be therapeutic when administered parentally. For reviews of killer toxin/antibodies the reader is referred to Marquina et al [49], Magliani et al [55], and Schmitt and Breinig [40].…”
Section: Mycoviruses and Toxinsmentioning
confidence: 99%